(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: Since ancient times, Central Asia has been one of the centers of science, culture, spirituality and enlightenment, which has raised thousands of world-famous great figures. Our great ancestors directly participated in the creation of a universal civilization and made a huge contribution to the development of spirituality and enlightenment alongside with mathematics, medicine in the region. The article discusses contributions of great scientists to the development of science in Central Asia.